2012
DOI: 10.1021/jp3026336
|View full text |Cite
|
Sign up to set email alerts
|

l-Arabinose Conformers Adsorption on Ruthenium Surfaces: A DFT Study

Abstract: Adsorption of 5 L-arabinose tautomers – one acyclic and four cyclic (α and β, pyranose and furanose) species – on a ruthenium surface was studied as a precursor-process of the, nowadays more and more, industrially important sugar catalytic hydrogenation on metal surfaces in water medium. The study was mostly referred to a 37-atom metal catalyst fragment, even though border-effects on the adsorption processes were also checked employing a 61-atom metal fragment. In order to figure out conformational effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The first affects the interaction geometry of the two surface binding modes, the second conversely rules the occurrence of single or multiple adsorption on the two metallic planes. It is interesting to note that along the adsorption process, the conformation of a-D-glucopyranose is retained, irrespective of the implicated binding modes [7]. Very similar geometries and interaction energies are found if the a-D-glucopyranose adsorbs on the unsupported Pd 30 .…”
Section: Adsorption Of A-d-glucopyranose Onto the Clustermentioning
confidence: 91%
See 1 more Smart Citation
“…The first affects the interaction geometry of the two surface binding modes, the second conversely rules the occurrence of single or multiple adsorption on the two metallic planes. It is interesting to note that along the adsorption process, the conformation of a-D-glucopyranose is retained, irrespective of the implicated binding modes [7]. Very similar geometries and interaction energies are found if the a-D-glucopyranose adsorbs on the unsupported Pd 30 .…”
Section: Adsorption Of A-d-glucopyranose Onto the Clustermentioning
confidence: 91%
“…While early results showed that more than 700 conformations are possible [9], the D-glucose in water is found almost exclusively in the a closed pyranose form. Even considering that the conformational ensemble of the a-D-glucopyranose could be small if adsorbed on a metal surface as, for example, already found for similar sugars adsorbed on ruthenium [7], the number of different conformations to take into account in a systematic investigation would be prohibitively high. For this reason, in the present study we used only the most stable a-D-glucopyranose conformation obtained in gas phase by Corchado et al [6] through a combined molecular dynamics and DFT study.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The optimization of dye/(TiO 2 ) 38 systems was performed using the SIESTA ab initio package, [43][44][45] the reliability of which has been proved by lots of related investigations and could give a good balance between accuracy and computational cost. [46][47][48][49][50][51][52][53] The computational details about SIESTA are given in the ESI. † Based on the optimized geometries, the partial density of states (PDOS) profiles on TiO 2 were evaluated at the PCM-M06/SVP level of theory through single point calculations using the Gaussian code.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The molecule energy and structure of different conformers of C5-PFK molecule differ, which lead to the difference of required energy for decomposition during discharge or heating, and may also affect the transition state and decomposition pathway to some extent [20]- [22]. When C5-PFK molecule participates in the adsorption or chemical reactions on solid (metal materials or organic insulating material) surfaces, the C5-PFK conformers have different range of molecular frontier orbitals or adsorption site, which may influence the reaction mechanism between the gas-solid interface [23]- [25]. Therefore, conformation analysis of C5-PFK molecule has certain guiding significance for its further study.…”
Section: Introductionmentioning
confidence: 99%